A study on the factors influence teachers’ attitude toward organizational change: A case study of secondary school, Kota Setar - Marini, Othman (2014)
This study aims to identify the factors that influence teachers’ attitudes towards organizational change in secondary school, Kota Setar. The objective of this study is to find an answer accurately and concrete about the relationship between the five independent variables; quickness acceptance of change, readiness to change, commitment in the organization, trust in management and communication in the organization that's influence the teachers' attitude toward organizational change for secondary school. In order to find out the relationship, 335 questionnaires have been distributed to teachers in secondary schools, Kota Setar, and found that 80.3% of respondents have returned their questionnaires. The method used in this study is a quantitative method. The study found that five of the eight key variables; readiness for change, quickness acceptance of change, commitment in the organization, belief in management and communication in the organization have significant impact on the attitude towards organizational change. This research is expected to provide benefits and improvements to at least two areas, management and practical implications. Quickness acceptance to change was found to be the most important factor in explaining the attitude towards organizational change that has the highest beta value of .465